Strategi Komunikasi Dinas Parawisata Kabupaten Maluku Tenggara dalam Promosi Objek Wisata Daerah - Vransisca Kissya (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2024)
Communication is one of the most important parts in marketing the tourism sector in a region. This is supported by the rapid development of technology and information in the digital era which makes it easy for everyone to enjoy the beauty of tourism, either indirectly. The purpose of this research is to find out how the strategy of the Southeast Maluku Tourism Office in promoting its tourism objects, besides knowing the inhibiting factors in promoting Southeast Maluku tourism objects. This research method is qualitative research using descriptive methods, namely by describing the data by describing, giving a picture that is collected then concluded. The techniques used to collect data are using observation, interview, and documentation methods. By using the four Indicators approach according to Chandler, the results showed that the strategy carried out by the Southeast Maluku Tourism Office in promoting its tourism objects uses human resource empowerment by conducting socialization, training and event creation, as well as utilizing the development of information and communication technology, while the inhibiting factor is the lack of funds and adequate infrastructure allowances.